Pengaruh Gaya Hidup, Marketing Effect, Modernitas Individu dan Kontrol Diri terhadap Perilaku Konsumtif Belanja Online Mahasiswa: (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam UIN K.H. Abdurrahman Wahid Pekalongan) - Estu Pramudita; Dwi Novaria Misidawati (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This study aims to analyze the influence of lifestyle, marketing effect, individual modernity, and self-control on the online shopping consumptive behavior of students at the Faculty of Islamic Economics and Business, UIN K.H. Abdurrahman Wahid Pekalongan. The phenomenon of online shopping has been increasingly prevalent in today's era, in line with the rapid development of digital technology and the internet, especially among students. As part of the digital generation, students have easy access to the internet, where nearly every activity is intertwined with internet usage, particularly on online shopping platforms. This research is a field study using a quantitative approach. A questionnaire was distributed to 96 respondents, students of the Faculty of Islamic Economics and Business at UIN K.H. Abdurrahman Wahid Pekalongan. The sample size was determined using purposive sampling based on predetermined criteria. The analysis methods used include instrument testing (validity and reliability tests), multiple linear regression, classical assumption tests (normality, heteroscedasticity, multicollinearity tests), and hypothesis testing (T-test, F-test, coefficient of determination test). The data were processed using SPSS Statistics 29. The results of the study indicate that: 1) The lifestyle variable does not have a significant effect on online shopping consumptive behavior, with a t-value of (1.563) < t-table (1.986). 2) The marketing effect variable significantly influences online shopping consumptive behavior, with a t-value of (4.495) > t-table (1.986). 3) The individual modernity variable significantly influences online shopping consumptive behavior, with a t-value of (2.111) > t-table (1.986). 4) The self-control variable significantly influences online shopping consumptive behavior, with a t-value of (3.173) > t-table (1.986). Simultaneously, lifestyle, marketing effect, individual modernity, and self-control all significantly influence online shopping consumptive behavior, with an F-value greater than the F-table (F-value 37.079 > F-table 2.47).